Evaluation of certain food additives and contaminants : seventy-seventh report of the Joint FAO/WHO Expert Committee on Food Additives. (Technical report series (World Health Organization) ;)
This report represents the conclusions of a Joint FAO/WHO Expert Committee convened to evaluate the safety of various food additives and a food contaminant with a view to concluding as to safety concerns and to preparing specifications for identity and purity. The first part of the report contains a general discussion of the principles governing the toxicological evaluation of and assessment of dietary exposure to food additives. A summary follows of the Committee's evaluations of technical toxicological and dietary exposure data for seven food additives (advantame; glucoamylase from Trichoder.